Central amygdala mineralocorticoid receptors modulate alcohol self-administration. (15th December 2020) - Makhijani, Viren H.; Irukulapati, Preethi; Van Voorhies, Kalynn; Fortino, Brayden; Besheer, Joyce
Abstract: The mineralocorticoid receptor (MR) is an emerging target in the field of alcohol research. The MR is a steroid receptor in the same family as the glucocorticoid receptor, with which it shares the ligand corticosterone in addition to the MR selective ligand aldosterone. Recent studies have shown correlations between central amygdala (CeA) MR expression and alcohol drinking in rats and macaques, as well as correlations between aldosterone and alcohol craving in individuals with alcohol use disorder (AUD). Additionally, our previous work demonstrated that systemic treatment with the MR antagonist spironolactone reduced alcohol self-administration and response persistence in both male and female rats. This study examined if reductions in self-administration following MR antagonist treatment were related to dysregulation of MR-mediated corticosterone negative feedback. Female rats treated with spironolactone (50 mg/kg; IP) showed increased plasma corticosterone following self-administration, which correlated with reduced alcohol self-administration. Next, local microinjection of the MR-selective antagonist eplerenone was used to identify the brain-regional locus of MR action on alcohol self-administration. Eplerenone infusion produced dose-dependent reductions in alcohol self-administration in the CeA, but had no effect in the dorsal hippocampus. Finally, to assay the functional role of CeA MR expression in alcohol self-administration, CeA MR was knocked down by antisense oligonucleotide (ASO) infusion prior to alcohol self-administration. Rats showed a transient reduction in alcohol self-administration 1 day after ASO infusion. Together these studies demonstrate a functional role of CeA MR in modulating alcohol self-administration and make a case for studying MR antagonists as a novel treatment for AUD. Highlights: Spironolactone reduced alcohol self-administration and increased corticosterone. MR antagonist eplerenone in CeA, but not dHC, reduced alcohol self-administration. Knockdown of CeA MR produced transient reductions in alcohol self-administration.